Technologically organized instructional process of higher education (Educational Dimension, 2022)
The article is devoted to one of the topical issues of professional and practical training of competitive specialists in higher education institutions of Ukraine. The focus is on improving the organization of the educational process and its technology. Using modeling as one of the relevant methods of pedagogical research, the paper presents and theoretically substantiates the author's model of organization of the educational process in higher education, which acts as a functional system for organizing the assimilation of knowledge by students of higher education institutions, the ways and means of this assimilstion in professional, practical and general cultural aspects. The structure of the proposed model of organization of the educational process in higher education consists of target, theoretical and methodological, content, technological, reflective-analytical, performance-evaluation blocks, each of which received a detailed description taking into account the specifics of their components.
Keywords: professional training; practical training; technologicalization of educational process; model of organization of educational process; higher education